RELEVANCE OF PREVENTION OF OBESITY CAUSED BY UNHEALTHY NUTRITION - Sabina Sayfiddinovna Saidova,; Guloyim Sultanboyevna Sobirova, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Obesity is a multifactorial condition whose development involves, in addition to an imbalance between energy intake and expenditure, various neurohumoral mechanisms and environmental factors. A high-calorie diet and a sedentary lifestyle are among the most important causes of obesity [1]. Obesity is currently considered a chronic, progressive disease characterized by excessive fat deposition in the body. Obesity is a chronic disease characterized by excess accumulation of body fat, which poses a health risk and is a major risk factor for a number of other chronic diseases, including type 2 diabetes mellitus (T2DM) and cardiovascular disease (CVD). The mechanisms underlying obesity are numerous and not fully understood. The most important factor in the development of the disease is excessive exogenous intake of easily oxidized lipids and their deposition in adipocytes. As the volume of metabolically active adipose tissue increases, the natural mechanisms regulating many physiological processes in the body are altered. Increased production of resistin, an insulin antagonist, inhibits insulin-dependent lipid breakdown. The sensitivity of the central nervous system to leptin, a hormone that regulates eating behavior, is significantly reduced. A vicious cycle of pathogenicity develops.